A Framework For Behavioural Intentions To Adopt Cryptocurrency Among Public University Students In The Kingdom Of Saudi Arabia - Saeed A., Alomari Ali (2024)
By examining individual intentions, this study seeks to provide valuable insights into the behavioural drivers and barriers affecting cryptocurrency adoption. The study used a quantitative research method with developing a survey questionnaire. Using a purposive sampling technique, the study targeted the students in the Saudi Arabian universities. The study used SPSS software for demographic and descriptive statistics and Smart PLS for testing validity, reliability and research hypotheses.